1998
DOI: 10.1046/j.1365-2958.1998.01027.x
|View full text |Cite
|
Sign up to set email alerts
|

Yeast gene YRR1, which is required for resistance to 4‐nitroquinoline N‐oxide, mediates transcriptional activation of the multidrug resistance transporter gene SNQ2

Abstract: SummaryWe have cloned and characterized a Saccharomyces cerevisiae gene YRR1 that is important for resistance to the mutagen 4-nitroquinoline N-oxide (4-NQO). The wild-type YRR1 gene encodes a protein that contains a Zn(II) 2 Cys 6 -type zinc-finger motif. Disruption of the YRR1 gene leads to hypersensitivity to 4-NQO. A dominant mutation (YRR1-1 ) that confers strong resistance to 4-NQO has been identified. Epistasis analysis demonstrated that 4-NQO resistances mediated by the YRR1 and YRR1-1 alleles require … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 28 publications
(51 reference statements)
4
66
0
2
Order By: Relevance
“…However, Wehrschutz et al (23) have shown that the deletion of both PDR1 and PDR3, despite strongly reducing PDR5 basal expression, does not abolish the induction of this gene upon cycloheximide or diazaborine treatment. Similar results have been reported for the ABC transporter Snq2p, the expression of which is slightly up-regulated by 4-nitroquinoline (4-NQO) independent of PDR1 and PDR3 (24).…”
supporting
confidence: 86%
“…However, Wehrschutz et al (23) have shown that the deletion of both PDR1 and PDR3, despite strongly reducing PDR5 basal expression, does not abolish the induction of this gene upon cycloheximide or diazaborine treatment. Similar results have been reported for the ABC transporter Snq2p, the expression of which is slightly up-regulated by 4-nitroquinoline (4-NQO) independent of PDR1 and PDR3 (24).…”
supporting
confidence: 86%
“…was originally cloned by its ability to confer reveromycin A resistance (17). Our data previously implicated YOR1 in resistance to both reveromycin A (7) and the mitochondrial ATPase inhibitor oligomycin (6).…”
Section: Yrr1 Confers Oligomycin Resistance In S Cerevisiae-yrr1mentioning
confidence: 95%
“…PB4 is a pdr1⌬ and pdr3⌬ mutant yeast strain as previously described (19). XZY1 and XZY2 were made by transforming a yrr1-⌬1::TRP1 gene disruption plasmid (17) digested with BamHI and PstI into SEY6210 and PB4, respectively. Trp ϩ transformants were selected and analyzed by Southern blotting analysis to confirm introduction of the disruption allele.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcription of PDR5, SNQ2, PDR10 and PDR15, as well as YOR1 (Table 2) is controlled by Pdr1p/Pdr3p and Yrr1p, the latter modulating expression of both SNQ2 and YOR1 [63,64]. PDR3 and YRR1 are also autoregulated via PDREs in their own promoters [63][64][65].…”
Section: Regulation Of Abc Gene Expression In S Cerevisiaementioning
confidence: 99%